Deteksi Dini Banjir dengan SIMOBI: Integrasi IoT dan Mobile - Winanti; Fernando, Andhika; Yudhatama, Dhimas; Wisnu Murti, Nugroho; Hussein Hamid, Muhammad; ., Adiyanto; Fernando, Erick (Jurnal Pekommas, 2024)
Tangerang Regency as a city of a thousand industries as well as a buffer for the capital city, is densely populated and often experiences flooding every rainy season. Losses from flood disasters can cause damage and disruption of economic activities and even loss of life. Efforts to minimize losses and loss of life due to flood disasters with early detection tools through the Flood Monitoring Application (SIMOBI). The purpose of creating SIMOBI for early detection of floods so that damage, disruption of economic activities and loss of life can be minimized. This research is a system development to find solutions for early flood detection in Tangerang Regency using the Prototype method and the system results are validated through Black Box Testing. This system is designed using the IoT (Internet of Things) principle which uses an internet network to connect the NodeMCU ESP 8266 microprocessor device with sensor and actuator devices. The NodeMCU ESP 8266 microprocessor to read water level data provided by the Ultrasonic sensor then sends data using the internet to a Smartphone with software that has been created to provide flood indication notifications. In addition to notifications from the Smartphone, a buzzer or siren is used to make a sound if there is an indication of flooding. The system works automatically if the water level exceeds the normal limit at the location and will send a notification via Smartphone and voice. This system is implemented in various flood-prone areas in Tangerang Regency such as Balaraja, Pasar Kemis, Cikupa, Curug, Cisoka, Gunung Kaler, Kelapa Dua, Jayanti, and Jambe.